Sentidos de arte como prática de cuidado na perspectiva de pessoas com transtorno mental - Araújo, Sicília Maria Moreira de (2011)
The art has been adopted as strategy and resource to health promotion that meets the practice of deinstitutionalization. On the other hand, it appears that the use of such resource sometimes disparage people with mental disorders. This study has as overall objective understand the meaning of art in mental health care given by people with mental disorder, accompanied by the Bom Jardim’s Communitarian Mental Health Care Movement (MSMCBJ) in Fortaleza, Ceara, acting jointly with the Municipality of Fortaleza through the Center for Psychosocial Care (CAPS) in the monitoring of this study’s participants. Such experience raises questions that guide this research because this Movement aims beyond the traditional pinelians practices still strongly conveyed to health treatment which uses essentially the medication as treatment. In this matter, art arises as a tool and way of health promoting, among other features. To understand how this strategy has reverberated in the health of users of health services from their own points of view, it was used as theoretical support Rotelli, Merhy, Amarante, Duarte Junior, Dimenstein and Boff with regard to the issue of health care practices. In relation to art, this survey was based on the theoretical support ideas from Paz, Ostrower and Vygotsky. In the historical-cultural perspective, Vygotsky, Pino, Lane, Molon, Aguiar and Namura were addressed. Methodologically, it was utilized qualitative research and cultural-historical approach in a case study of the Bom Jardim’s Communitarian Health Care Movement (MSMCBJ). The frame time of the survey was developed two focal groups. The first occurred in August 2009 and the second in October 2009. The two focal groups were conducted with the participation of users of the health service of MSMCB. The first focal group was conducted with nine people. This group’s theme was mental health care; and the second group, with six people, used the theme of art as care. In both moments only one of them was accompanying a research’s participant. Content analysis was used as a method of data analysis in this study. The results pointed to a user’s perspective of valuation of a care practice that asked certain specific key to building relationships between professionals and patients which were reported as the exercise of freedom of expression, practice autonomy, exercise of valuing oneself and interacting with other individuals, with the consequent development of the participants as social subjects. The use of art in mental health care showed the significance of this fundamental part of mental health care. The characteristics of the context of working with art appeared as facilitators of healthy relationships between users and professionals.